Blood pressure patterns in women with gestational hypertension or mild preeclampsia at term. (March 2017) - van der Tuuk, K.; Tajik, P.; Koopmans, C.M.; van den Berg, P.P.; Mol, B.W.J.; van Pampus, M.G.; Groen, H.; ,
Abstract: Objective: Gestational hypertension (GH) and mild preeclampsia (PE) represent the most common medical complications of pregnancy, with the majority of cases developing at or near term. There is little knowledge of the course of blood pressure over time in these women. We explored the pattern of systolic and diastolic blood pressure over time in women with GH or mild PE at term participating in the HYPITAT trial, and we attempted to identify clinical factors influencing these blood pressure patterns and the impact of severe hypertension on clinical management. Study design: We used data from the HYPITAT trial, that included women with a singleton pregnancy with a fetus in cephalic position between 36 and 41 weeks of gestation with the diagnosis of GH or mild PE. Blood pressure measurements were performed from randomization or admission until delivery or discharge from the hospital. We included the highest blood pressure of each day. We evaluated systolic and diastolic blood pressure change over time, as well as the influence of clinical characteristics and laboratory findings on the course of blood pressure. We used univariate and multivariate regression analysis with a backward stepwise algorithm for the selection of variables. The model with the best fit (lowest AIC) was selected as the final model. We also compared mode of delivery for women with and without severe hypertension. Results: We studied 1076 women who had 4188 blood pressure measurements done. The systolic blood pressure showed a significant non-linear increase over time and for the diastolic blood pressure the pattern was also non-linear. In the multivariable model of systolic blood pressure change over time, nulliparity, ethnicity, systolic blood pressure (at baseline), BMI and LDH at randomization influenced the course of blood pressure. In the diastolic blood pressure model ALT and the baseline diastolic blood pressure had a significant influence. When we explored the association between blood pressure and mode of delivery, it appeared that development of severe hypertension was a risk factor for Caesarean section. Conclusion: The blood pressure in patients with GH or PE at term showed a non-linear increase with time, which was aggravated by clinical characteristics. Development of severe hypertension was a risk factor for Caesarean section, which may explain the elevated Caesarean section rates in the expectant monitoring group in the HYPITAT trial.